Early stabilization of the uncemented Symax hip stem in a 2-year RSA study - Kruijntjens, Dennis S M G; Koster, Lennard; Kaptein , Bart L; Jutten , Liesbeth M C; Arts, Jacobus J; Broeke, René H M Ten (Acta Orthopaedica, 2020)
Background and purpose — The uncemented Symax hip stem has shown early proximal ingrowth as result of the BONIT-hydroxyapatite (HA) coating and the distal DOTIZE surface treatment. We evaluated 2-year postoperative radiostereometric analysis (RSA) migration of the Symax hip stem in THA patients. We also investigated the correlation between migration at 4 weeks and clinical outcomes after 2 years. Patients and methods — Patients in a 2-year clinical follow-up single-centre RSA randomized controlled trial were randomized to 2 different cup designs. All 45 patients received a Symax hip stem. RSA migration patterns of the Symax hip stem is presented here as a single cohort. RSA examinations were performed postoperatively, but before weight-bearing, and subsequently after 1, 3, 6, 12, and 24 months. Clinical outcomes and radiographic evaluations were assessed 3, 6, 12, and 24 months postoperatively. Results — During the first 4 weeks, the Symax hip stem subsided, rotated into retroversion, and translated posteriorly, after which the migration ceased and the prosthesis stabilized. All clinical outcomes improved from preoperatively to 2 years. There was no clinically or statistically significant correlation between subsidence and retroversion at 4 weeks and clinical outcomes after 2 years. Interpretation — RSA evaluation of the uncemented Symax hip stem confirms that the design principles and coating properties lead to early stabilization of the stem, as early as 4 weeks postoperatively. There was no correlation between subsidence and retroversion at 4 weeks and clinical outcomes after 2 years. Based on the predictive potential of the RSA technique, we anticipate excellent long-term survival of this hip stem.